Imprisoned: Interlocking Oppression in Law Enforcement, Housing, and Public Education - Meyerhoffer, Cassi A.; Rodriguez, Brittany Leigh (University of Georgia Press, 2023)
Over the last several years, the United States has experienced a surge in bystander videos that have captured incidents of police brutality and prejudice directed largely at Black people. Public outrage surrounding police brutality persists as these incidents continue to reach the public eye. As public discourse around police brutality and racial inequality largely centers on specific events, there is a dearth of information about systemic racism and how race and racism pervade every single aspect of American life. How Black people are often treated by law enforcement is reflective of larger historical racial inequities and injustices that extend far beyond the criminal justice system and intersect with how Black people access housing, occupy public spaces, and are treated in American public schools.Imprisoned: Interlocking Oppression in Law Enforcement, Housing, and Public Educationfocuses on contemporary systemic racism as it relates to how the U.S. criminal justice system, housing system, and education system intersect to create a matrix of inequality for Black people. To illustrate the systemic nature of racism in American policing and communities, this book highlights contemporary policies and practices that intersect with residential segregation and public schooling that continue to affect Black people on a large-scale, structural level―demonstrating the extent to which the United States criminal justice system is tied to where people live and how they are treated and educated in public schools.
Keywords: dept.soc